Constituents from the Seeds of Sophora Alopecuroides L. - Rong, Zi-Jian (Molecules, 2020)
Three new isoflavone glucosides, kudonol A−C (1–3), two new ester derivatives of phenylpropanoid, kudolignan A and B (4–5) and five known compounds, (−)-maackiain (6), neoliquiritin (7), methyl 4-coumarate (8), methyl ferulate (9) and (+)-wikstromol (10), were isolated from an extract of dried seeds of the traditional Chinese medicinal plant Sophora alopecuroides L. Their structures were established by NMR and HRESIMS data analyses. The monosaccharide part’s configuration of isoflavone glucosides was confirmed by acid hydrolysis and analyzed by a JAsco OR-4090 chiral detector, comparing it to standard substance D-glucose. The cytotoxicity effects against HeLa, Hep3B, MCF-7 and H1299 cells were tested by CCK-8 assay.